Producing chitosan from shellfish waste and its application as a natural coagulant in water purifiers - Feerzet Achmad; Rifka Noor Azizah; Yuliana Daulay; Reni Yuniarti; Suharto Suharto; Suhartono Suhartono; Siti Rizkyna Noorsaly (Konversi, 2024)
Waste from simping shellfish (Amusium pleuronectes) shells can pose environmental hazards if waste levels exceed the threshold. This research aims to produce chitosan from shellfish, specifically simping shells, for the purification of raw water. The optimal dosage for both chitosan and alum coagulants in water samples with bay river turbidity (49.5 NTU) is 1 ppm, resulting in a turbidity removal percentage of 99%. The optimum pH for chitosan coagulant (1 ppm) is 6.32, and for alum coagulant (1 ppm) is 8. For bay river water with an initial turbidity of 49.5 NTU, the optimal dose of chitosan coagulant is 1 ppm, achieving a turbidity removal percentage of 99%. Producing chitosan from shellfish waste as a natural coagulant for water purification offers an eco-friendly, cost-effective solution that enhances water quality, reduces seafood industry waste, and provides a safe alternative to chemical coagulants, with potential applications in various fields.